Analisis Pendapatan dan Komposisi Agroforestry Petani di Desa Merbaun, Kecamatan Amarasi Barat, Kabupaten Kupang, Provinsi Nusa Tenggara Timur - Sion Christanto Kaho Hinga; Wilhelmina Seran; Nixon Rammang (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2023)
The purpose of this study was to determine the agroforestry system and the amount of income from the agroforestry system generated by the community in Merbaun Village, West Amarasi District, Kupang Regency. This research was conducted in Merbaun Village, West Amarasi Subdistrict, Kupang Regency, East Nusa Tenggara Province. The sample selection was carried out in a purposive manner. Data collection techniques used in this study were primary data and secondary data. From the data collected, descriptive and quantitative data analysis was conducted. The results showed that Agroforestry applied by farmers from Merbaun Village is an agroforestry system that has existed for generations and uses traditional methods, namely by combining agricultural crops, forestry and livestock or what is usually called Agrosilfopasture. With a management system like this can increase the productivity of farmers in a land. The composition of plant species found in Merbaun Village is Coconut (Cocos Nucifera L), Banana (Musa Paradisiaca), Corn (Zea Mays ssp), Teak (Tectona grandis), White teak (Gmelina Arborea), Mahogany (Swetenia machrophylla), Areca nut (drera catechu L), cassava (Manthot Esculente), Johar (Cassia siamed). The total average income earned by farmers from agroforestry results in Rp 25,289,875- per year.